Conflict or synergy? Analysis of economic-social- infrastructure-ecological resilience and their coupling coordination in the Yangtze River economic Belt, China. (September 2022) - Lin, Yingzi; Peng, Chong; Chen, Peng; Zhang, Mengjie
Highlights: A spatiotemporal analysis of economic-social-infrastructural-ecological resilience was provided. An entropy weight-TOPSIS and CCD model were used to reveal interactions between urban resilience subsystems. The interactions within urban resilience in the YREB was characterized by increasing regional disparity. Optimal strategies and policy implications for the YREB were put forward. Abstract: Urban resilience is a highly integrated system with multiple dimensions involving dynamic transformations and interactions across dimensions. It is crucial for urban sustainability to investigate the coupling coordination relationships between urban resilience subsystems. We used data from 126 cities in 2008, 2012, and 2017 in the Yangtze River Economic Belt (YREB) in China, the entropy weight-TOPSIS method, and a coupling coordination degree (CCD) model to quantify the economic, social, infrastructure, and ecological resilience and the coupling coordination relationships. The results indicated that the economic resilience (EnR), infrastructure resilience (IR), and ecological resilience (ElR) indices exhibited a non-steady increasing trend, whereas the social resilience (SR) index gradually decreased over time. Spatially, the EnR and SR indices decreased from the eastern to the central and western cities, and the IR and ElR indices had high values in the east and west and low values in the midstream region. Interestingly, the midstream region was the only one showing a dramatic decline in the SR and ElR indices, whereas the upstream and downstream areas maintained a steady growth trend for all four indices. Further, the YREB was dominated by cities with high IR and ElR indices, showing a gradual decline in the number of resilience patterns. Combined with the overall and pair-wise coupling coordination results, our findings indicate that the four subsystems were in moderate imbalance. The upstream and midstream regions remained in moderate imbalance, but the downstream regions changed from moderate imbalance to low coordination. Moreover, the interactions of EnR-IR, EnR-ElR, and IR-ElR changed from moderate imbalance to low coordination, and the other pairs of subsystems remained in moderate coordination. This paper sheds new light on the internal mechanism of urban resilience and provides references for practical interventions and policymaking for sustainable urban development.